THE IMPACT OF INTERNAL COMMUNICATION ON ACHIEVING ORGANIZATIONAL OBJECTIVES - Mihlayifani Nicholas Nyoni; Siew Poh Phung; Valliappan Raju (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Internal communications is the lifeline of any existing organization. Internal communication spans from the two-way communication channels, to internal branding. Internal branding has been seen to propel the marketing drive to alarming levels. A focus on internal communication with such variables as productivity and internal branding are the subject of the study. The study considered small and medium enterprises in Selangor area in Malaysia. The quantitative approach was employed into the study and a sample of one hundred and seventy participants were obtained successfully.